The Function of Music in Silek Minangkabau: Instrument and Cultural Values - Rosta Minawati; Alfalah Alfalah (Gondang: Jurnal Seni dan Budaya, 2025)
Silek minang is a form of traditional martial arts originating from Minangkabau, West Sumatra. This martial art consists of physical aspects and fighting techniques accompanied by music. The music has an important role and function in supporting the players' emotions, serving to enhance and support the movements and providing a heroic atmosphere in the silek performance. This article examines the musical instruments used in silek minang music and its function. This research used a qualitative approach with observation and interviews with artists, cultural figures, community leaders, Silek practitioners and traditional musicians. Our results show that each of the accompanying instruments for the silek minang including talempong, gandang tambua, gandang tasa, sarunai and gong, has a specific function and role in supporting silek in performance. The sounds and rhythms promote the player's emotional engagement when carrying out silek movements. Enthusiasm is brought about by the influence of the rhythm of loud music and a faster or slower tempo in stimulating the atmosphere. The music is at once a symbolic marker, event opener, and encouragement to players and audience. Symbolic interactions between performers, musicians and audience are co-present in the performance space in a dynamic and lively atmosphere.